Uji Efektifitas Ekstrak N-heksan Kulit Duku (Lansium domesticum corr) Terhadap Telur Nimfa Dan Kutu Dewasa Pediculus humanus capitis - Darmadi Darmadi; Ayesha Nurul Fitri (Jurnal Ilmu Kesehatan Abdurrab, 2025)
Pediculosis is a head lice infection caused by Pediculus humanus capitis, which commonly occurs, especially among school-aged children. The typical approach to treating pediculosis involves the use of chemical insecticides; however, these are not environmentally friendly. Therefore, alternative treatments using natural ingredients, such as duku (Lansium domesticum Corr.) peel extract, are needed. This study aims to examine the effectiveness of the N-hexane extract of Lansium domesticum peel against the mortality of nymphs, adult lice, and the microscopic condition of lice eggs (Pediculus humanus capitis). This research used an experimental method with a post-test only control group design. The results showed that the percentage of inactive egg stages was 100% at a 20% concentration, 90% at 15%, and 70% at 10%. Nymph mortality was 80% at 20% concentration, and 60% at both 15% and 10%. Adult lice mortality was 80% at 20%, 20% at 15%, and 0% at 10%. The conclusion of this study is that the N-hexane extract of Lansium domesticum peel can act as a natural insecticide against lice eggs, nymphs, and adults.